Application of peripheral blood cytokine and immunoglobulin detection in ACTH therapy for the treatment of infantile spasms - Wang, Xiaocui; Huang, Qin; Wu, Lulu; Yang, Yang; Ye, Xiaofei; Yang, Bin (Frontiers in Pediatrics, 2024)
Objective This research aims to investigate the levels of lymphocytes, immunoglobulins, and cytokines in children with infantile spasms (IS) before and after adrenocorticotropic hormone (ACTH) therapy and to explore the application of these markers in evaluating the therapeutic effects of ACTH on infantile spasms. Methods From May to November 2022, 35 children initially diagnosed with IS and treated at our hospital were regarded as the observation group, and 35 healthy children who underwent physical examination at our hospital during the same period were regarded as the control group. Children in the observation group received intramuscular injections of ACTH for 2 weeks. Fasting venous blood was collected from the control group and the observation group before and after ACTH therapy. Serum levels of immunoglobulins IgG, IgA, and IgM in serum were detected by immunoturbidimetry. T-cell subsets (CD3+, CD3+CD4+, and CD3+CD8+) and B-cell subsets [CD3−CD19+ and CD3−CD16+CD56+ natural killer (NK) cells] were detected by flow cytometry, and the ratio of CD3+CD4+/CD3+CD8+ was calculated. Serum levels of interleukin-1β (IL-1β), interleukin-2R (IL-2R), and interleukin-6 (IL-6) cytokines were detected by the enzyme-linked immunosorbent assay, and changes in serum cytokine and immunoglobulin levels in the two groups were compared before therapy, whereas in observation group one, these comparisons were made both before and after ACTH therapy. Results Compared to the control group, the observation group showed significantly increased serum levels of immunoglobulins IgG and IgM before therapy, while the level of IgA was significantly decreased (p < 0.05). Also, the percentage of CD3−CD19+ B cells was significantly increased, while the percentages of CD3+ T cells and CD3+CD4+ T cells were significantly decreased (p < 0.05). The percentages of CD3+CD8+ T cells, CD3−CD16+CD56+ NK cells, and CD3+CD4+/CD3+CD8+ cells did not change significantly (p > 0.05); the levels of cytokines IL-1 β, IL-2R, and IL-6 were significantly increased (p < 0.05). Compared to levels before treatment, the serum level of immunoglobulin IgG in the observation group after ACTH therapy was significantly reduced (p < 0.05), while the IgA and IgM levels did not change significantly (p > 0.05). The percentages of CD3+ T cells and CD3+CD4+ T cells were significantly increased, while the percentages of CD3−CD16+CD56+ NK cells and CD3−CD19+ B cells were significantly decreased (p < 0.05); however, the percentages of CD3+CD8+ T cells and the CD3+CD4+/CD3+CD8+ ratio did not change significantly (p > 0.05). Furthermore, the levels of cytokines IL-1 β, IL-2R, and IL-6 were significantly reduced (p < 0.05). Conclusion Children with IS exhibit immune dysfunction, and the changes in serological immune indices after ACTH treatment indicate that ACTH may control seizures in IS children by regulating and improving immune dysfunction. Therefore, the therapeutic effects of ACTH on IS can be evaluated by detecting the levels of cytokines and immunoglobulins.